Pengaruh Return On Asset, Return On Equity Dan Earnings Per Share Terhadap Harga Saham Pada PT Unilever Indonesia Tbk - Purba, Eka; Wahab, Wahyul (CIVITAS: Jurnal Studi Manajemen, 2021)
This study aims to determine whether there is an effect of return on assets, return on equity, and earnings per share on the company's stock price simultaneously and partially at PT. Unilever Indonesia, Tbk for the period 2010-2019. Types and sources of data in this study are secondary data in the form of financial statements of PT. Unilever Indonesia, Tbk in 2010-2019. The data analysis method used in this research is quantitative descriptive method and multiple linear regression analysis model, classic assumption test using normality test, multicolonearity test, heteroscedasticity test, and autocorrelation test, and hypothesis testing using the coefficient of determination (R2) test. simultaneous test (F test), and partial test (t test) with data processing using the SPSS Statistic 22 program. The results showed that the regression model is normal, multicolonearity does not occur, and autocorrelation does not occur, and the coefficient of determination (R2) test results 0.681 or 68.1% indicates that the variables return on assets, return on equity, and earnings per share are able to explain the variations that occur in the stock price of PT. Unilever Indonesia Tbk, while the remaining 31.9% is explained by other variables which are not researched. The results of the study partially show that return on assets has no and significant effect on stock prices and return on equity has no and insignificant effect on stock prices, while earnings per share has a significant and significant effect on stock prices. Meanwhile, simultaneously, return on assets, return on equity, and earnings per share have a positive and significant effect on stock prices.